Working mechanisms in positive interventions: A study using daily assessment of positive emotions. Issue 5 (2nd September 2020) - Gander, Fabian; Proyer, René T.; Hentz, Eva; Ruch, Willibald
ABSTRACT: One commonly suggested mechanism in positive psychology interventions (PPIs) involves the elicitation of positive emotions. We examined (1) whether PPIs increase the intensity and variety of positive emotions; (2) which positive emotions are elicited by two different PPIs; and (3) the impact of positive emotions on well-being. In a randomized, controlled one-week intervention study, we compared the 'three good things' and the 'three funny things' intervention with a placebo control. We assessed the positive and negative emotions reported daily during the intervention, and the well-being and depressive symptoms directly before, after, and one week after the intervention. Results showed higher intensity and variety of positive emotions elicited by the PPIs, and increases in well-being could be explained by the intensity and variety of positive emotions. The study provides a model for how the mechanisms underlying PPIs can be studied and underlines the relevance of positive emotions in PPIs.